Metajournalistic discourse on the rise of gaming journalism - Perreault, Gregory and Vos, Tim (New Media & Society, 2020)
Gaming journalism, which finds its origins in public relations-oriented gaming magazines, discursively attached itself to traditional journalism in the wake of the 2014 GamerGate controversy. Yet it had remained unclear where gaming journalism fits within the ecology of journalism. This study examines metajournalistic discourse regarding gaming journalism from 2010 to 2018 and analyzes 53 articles about gaming journalism from that period in order to understand how the broader journalistic field conceptualized gaming journalism’s place within it. This study argues that gaming journalism is discursively marked as a lower, marginal form of journalism based on perceived differences in professional values and journalistic savviness.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMTE3Ny8xNDYxNDQ0ODE5ODU4Njk1